Zdania afinitywne w ujęciu kontrastywnym i diachronicznym na podstawie wybranych fragmentów tekstu "Psałterza floriańskiego" = Affinitive sentences in a contrastive and diachronic approach based on selected fragments of the Florian Plaster`s text - Schönherr, Monika (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Despite the existence of various syntactic approaches, verbal sentences still prevail in the traditional grammar as a main research object. In contrast, verbless sentences, which do not contain a verb element, are not included in leading theoretical approaches to syntax. However, the very existence of these syntagms interrogates the traditional understanding of the concept of a sentence.
Keywords: afinitywność; zdanie bezczasownikowe; forma finitywna/osobowa czasownika; zdanie afinitywne; analiza korpusowa; Psałterz floriański; non-finiteness; verbless clauses; a finite verb; non-finite clauses; corpus-based analysis; Saint Florian Psalter